THE GROSS DOMESTIC PRODUCT ANALYSIS IN INDONESIA FOR 2008-2021 - Herlina, Listri; Permata Rahmi, Palupi (Universitas Indonesia Membangun (Inaba), 2022)
Economic growth is an indicator that plays an important role in determining the prosperity of a country. This study aims to analyse the effect of growth of foreign debt, inflation, Exchange rate, growth of poverty, and regional minimum wage on gross domestic product (GDP) in Indonesia for 2008 - 2021. Data collected through library research from the Central Bureau of Statistics and Bank Indonesia Reports. Furthermore, the data was processed using descriptive statistical analysis and verification. Ordinary Least Square regression analysis using EViews software approach was adopted for analyse the effect of independent variables on dependent variable. The result shows that gross domestic product (GDP) is influenced by the growth of foreign debt, the growth of poverty, and the growth of the minimum wage. This result is supported by the value of t-statistics < t table and also simultaneously through the coefficient of determination shows that the three variables above have a significant effect on the gross domestic product variable.